Beyond improvisation? The rise and rise of youth entrepreneurs in north India. Issue 1 (14th November 2016) - Young, Stephen; Kumar, Satendra; Jeffrey, Craig
Abstract : This paper draws on qualitative fieldwork conducted in 2004–5, 2010 and 2012 to examine the recent expansion of higher education markets in north India. It focuses on a group of young men who attended university in the city of Meerut, Uttar Pradesh. Faced with dismal job prospects, they began to improvise, making money ad hoc by acting as small‐scale political brokers on campus. However, some of them subsequently utilised these improvisational skills to try and attain loftier economic ambitions. As India's education sector was liberalised, they honed in on an opportunity to establish their own profitable colleges. Our paper points to a paradox that resonates far beyond India; namely, that the continued expansion of private education is, in some cases, happening in spite of and even because of poor job growth. We also extend recent work on the theme of improvisation. By examining long‐run changes, we show that improvisation is not indelibly linked to the activities of 'youth', but rather a set of practices that they may perform and abandon as they move through the life course. As such, improvisation can serve as a staging post in the efforts of young people to obtain a more secure foothold in the economy.